Assessing the Impact of the Independent Learning Curriculum: A Case Study in Elementary Schools - Rizka Safitri; Mohamad Agung Rokhimawan (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study evaluates the implementation of the independent learning curriculum in elementary schools using the Context, Input, Process, Product (CIPP) evaluation model. Addressing this curriculum's effectiveness is essential for enhancing educational quality, resources, teaching strategies, and student learning outcomes. A mixed-methods approach was adopted, involving qualitative interviews and quantitative questionnaires to collect data from a principal, a vice principal for curriculum, and 15 teachers. This dual approach enabled an in-depth examination of curriculum implementation factors. Analysis reveals that the independent learning curriculum is implemented effectively and efficiently. "Effectiveness" is defined as the curriculum’s success in meeting learning objectives, while "efficiency" refers to resource optimization in teaching. Despite these positive outcomes, the study identified notable challenges: limited teacher competency in assessments, inconsistencies in teaching methodologies, and constraints in available facilities and infrastructure. To address these challenges, several strategies are proposed: diversifying reference materials, establishing robust assessment formats, implementing game-based learning activities, promoting online self-training, and fostering stronger learning communities within schools. These strategies aim to mitigate the identified challenges and enhance curriculum delivery. Implementing the proposed strategies is expected to improve the effectiveness and efficiency of the independent learning curriculum, potentially leading to substantial improvements in student educational outcomes. This study highlights the need for continuous curriculum assessment and support for teachers to ensure sustained educational quality and effectiveness.